2019
DOI: 10.3390/su11133578
|View full text |Cite
|
Sign up to set email alerts
|

Thorny Shrubs Limit the Browsing Pressure of Large Herbivores on Tree Regeneration in Temperate Lowland Forested Landscapes

Abstract: Thorny shrubs are considered as an important driver in the natural development of temperate forest structures, particularly in European lowland forests. We assessed the current role of thorny shrubs in the regeneration of deciduous tree species under heavy browsing pressure in a central European temperate forested landscape. The study’s military training area offered a unique opportunity to investigate the processes in which deciduous tree seedlings grew under thorny shrubs and in the close vicinity of thorny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Also, the structural response of a particular plant to ungulate browsing may vary to such an extent that some parts of the tree will be readily eaten, while other parts will be less attractive (Hartley et al 1997); furthermore, the differences within one tree may be greater than those between two separate trees. On the other hand, the blackthorn’s spinescences are part of a well-known structural defence mechanism used against biotic stress factors (Pisani and Distel 1998; Scogings et al 2011; Salek et al 2019). We noticed that all heavily browsed blackthorns had thick, hard and well-developed thorns located on twigs of the external parts of the crowns, whereas on unbrowsed bushes such structures were less developed only on older twigs situated in the inner regions of the plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the structural response of a particular plant to ungulate browsing may vary to such an extent that some parts of the tree will be readily eaten, while other parts will be less attractive (Hartley et al 1997); furthermore, the differences within one tree may be greater than those between two separate trees. On the other hand, the blackthorn’s spinescences are part of a well-known structural defence mechanism used against biotic stress factors (Pisani and Distel 1998; Scogings et al 2011; Salek et al 2019). We noticed that all heavily browsed blackthorns had thick, hard and well-developed thorns located on twigs of the external parts of the crowns, whereas on unbrowsed bushes such structures were less developed only on older twigs situated in the inner regions of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…In a scenario where browsing is intense, individual plants can react by increasing the secretion of defensive compounds (Wigley et al 2015), developing structurally induced defences (Salek et al 2019), increasing foliar nitrogen (N) levels (Scogings et al 2011) or changing resource allocation patterns (Orians et al 2011; Scogings et al 2014; Peschiutta et al 2018). As plant defence systems may limit foraging preferences, ungulates have developed a number of strategies to counteract such systems, like avoidance behaviour, reducing the intake of certain food types (Iason and Villalba 2006) or physiological adaptation to tolerate toxic plant products with the aid of specific binding enzymes (Clauss et al 2003; Iason and Villalba 2006; Mlambo et al 2016; Perkovich and Ward 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Europe have shown that dense cover of some thorny shrubs, such as wild rose and hawthorn (Crataegus spp. ), can deter browsing of shade-tolerant regenerating hardwoods by red deer and sika deer (Cervus nippon), but that the protective effects of other shrubs, such as blackthorn (Prunus spinosa), are outweighed by competitive effects [88]. A study in Michigan found that weeding reduced the height of fast-growing hardwood species in harvest gaps by exposing them to browsing by white-tailed deer, but that slow-growing species did not benefit [41].…”
Section: Alternative Methodsmentioning
confidence: 99%
“…On the other hand, the impact of understory-associated vegetation on natural regeneration is complex. The diversity of shrubs and herbs contributes to the forest's water-holding capacity and nutrient retention [21]; for example, thorny shrubs can reduce browsing by herbivores [22], thereby increasing the survival rate of seedlings and saplings. However, shrubs may compete with tree seedlings [23].…”
Section: Introductionmentioning
confidence: 99%